(untitled) (Huellas, 2024)
Without avoiding the fact that memories imply a subjective process of selection and constitute an arena of dispute, as well as the consideration that the past implies uses that seek to legitimize specific discourses and practices, this text deals with the “original objectives” of the INTA made invisible since the state. The fundamental purpose is to demonstrate that, far from denying the social function of the institute, its initial goals recognized and actively addressed it. To achieve this goal, the historical discipline is used by virtue of its ability to provide a deeper understanding of the period referred to by the current policymaker.